Vegetation diversity based on peat hydrological units for supporting cattle production in West Kalimantan, Indonesia - DUTA SETIAWAN; ANURAGA JAYANEGARA; NAHROWI NAHROWI; NUR ROCHMAH KUMALASARI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Setiawan D, Jayanegara A, Nahrowi, Kumalasari NR. 2024. Vegetation diversity based on peat hydrological units for supporting cattle production in West Kalimantan, Indonesia. Biodiversitas 25: 2011-2019. This study determined the characteristics of forage supply, composition, and diversity in various West Kalimantan Peat Hydrological Units (PHU) and the capacity for livestock development. The methods used were a combination of surveys, direct observations, and measurements of samples of peat hydrological units commonly used as pasture by farmers. The results showed that the pattern of providing forage for livestock is that the majority of farmers are in the productive age category (41-60 years), the education level was only elementary school, livestock farming was only a side business (78.33-81.67%), and the mowing capacity was still above livestock feed requirements. Important Value Index (IVI) in Mempawah Ageratum conyzoides (32.34%), Pontianak IVI Digitaria sanguinalis (27.17%), Kubu Raya IVI Cyperus brevifolius (22.43%). The forage species diversity index (H) of the three districts in West Kalimantan was classified as moderate or high. The species Richness Indices (R') for Mempawah, Pontianak, and Kubu Raya were 5.01, 6.22, and 6.41, respectively. The carrying capacity index in Kubu Raya (2.01) and Mempawah (5.19) was included in the safety criteria because it has a CCI above 2. In conclusion, The West Kalimantan livestock population can be increased by utilizing land in rice fields, dry fields, community forests, and plantations as a source of diverse forage vegetation.